2014
DOI: 10.1182/blood-2014-09-599399
|View full text |Cite
|
Sign up to set email alerts
|

Five hematologic tests and treatments to question

Abstract: Choosing Wisely® is a medical stewardship initiative led by the American Board of Internal Medicine Foundation in collaboration with professional medical societies in the United States. The American Society of Hematology (ASH) released its first Choosing Wisely® list in 2013. Using the same evidence-based methodology as in 2013, ASH has identified 5 additional tests and treatments that should be questioned by clinicians and patients under specific, indicated circumstances. The ASH 2014 Choosing Wisely® recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 37 publications
(24 reference statements)
0
49
0
5
Order By: Relevance
“…Overdiagnosis and underdiagnosis of HIT have important medical and economic consequences. [24][25][26][27] Unfortunately, "gold standard" functional assays such as the SRA are not available in a timely manner in many medical centers. Therefore, an alternative assay that is rapidly and easily performed would be of significant utility.…”
Section: Discussionmentioning
confidence: 99%
“…Overdiagnosis and underdiagnosis of HIT have important medical and economic consequences. [24][25][26][27] Unfortunately, "gold standard" functional assays such as the SRA are not available in a timely manner in many medical centers. Therefore, an alternative assay that is rapidly and easily performed would be of significant utility.…”
Section: Discussionmentioning
confidence: 99%
“…These include: (1) increase in the number of commercially available immunoassays for HIT testing with variable performance characteristics, (2) testing algorithms that rely on screening with immunoassays, (3) increase of HIT testing in low-risk patients, and (4) over-reliance on EIA results (especially strong EIApositive results) without confirmatory SRA testing. In its 2014 "Choosing Wisely" initiative, the American Society of Hematology recommended the limited use of testing in suspected HIT patients with low pretest probability of HIT [31] because of the high rate of false-positive HIT test results when using immunoassays.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests a note of caution regarding application of the Choose Wisely recommendation 19 that advises against HIT testing in patients with a low pretest probability of HIT. We found that patients with a low 4Ts score had a frequency of HIT of 1.9%, but that frequency rose to 15% if the PF4/H-PaGIA result was positive.…”
Section: Discussionmentioning
confidence: 99%